(untitled) (Al Insyirah International Scientific Conference on Health, 2021)
Labor pain is a subjective experience of physical sensations associated with uterine contractions, dilation and thinning of the cervix. Most deliveries (90%) are accompanied by nyari. Non-pharmacological treatment with effleurage massage technique is an alternative to reduce labor pain when the active phase is active in primigravida mothers. An initial survey conducted at BPM Ernita on July 22 of 2 postpartum mothers said that during labor the mother felt pain. But only 1 mother who did light massage such as stroking all parts of the stomach and the mother said that it is more comfortable to do the method. The purpose of this study was to determine the relationship of effeluarge massage techniques to the reduction of pain intensity in the first phase of active phase in primigravida mothers. This type of quantitative analytic study is a quasi-experimental non-randomized pretest-posttest design approach. The population in this study were all primigravida mothers who performed labor. Based on the paired t test results that on average before doing 5.2308 and after 3.0769 with a P value of 0.000, which means ≤ from 0.05, so it can be concluded that there is a relationship between effleurage massage techniques to decrease the internal pain of labor in the first stage of the addictive phase in mothers primigravida at BPM Ernita. Midwives as executors in providing midwifery services are expected to be able to recognize every need of patients and their families and to provide IEC (communication, information, and education) on issues related to maternity pain, so that the effleurage massage technique is expected to be able to be used as a midwifery independent measure to reduce the level of pain.